OPTIMISING THE PERFORMANCE OF ROUNDABOUTS IN DAR ES SALAAM CITY - Mfinanga, David A (Tanzania Journal of Engineering and Technology, 2017)
Intersections are one of the major bottlenecks that aggravate congestion in road networks; effective control of which is an important strategy in improving traffic flow. While developing countries have found it hard to adopt sophisticated means of intersection control, they have also not optimised the performance of roundabouts. This paper reviews the performance of roundabouts, which have become increasingly popular in recent years, as simple and low cost forms of intersection control. The performance of three major roundabouts in Dar es Salaam has been analysed and results show that roundabouts can accommodate high traffic volumes without causing excessive delays. The results also show that low-cost improvements on roundabouts, involving minor adjustments in geometry and improved traffic management, can significantly improve their operational performance.